The impact of water flow rate on the dynamic dissolution kinetics of fractured limestone formations - Xu, Dabao; Ma, Yuhang; Feng, Bo; Fan, Mingming; Han, Zhenchuan (Frontiers in Earth Science, 2025)
To break through the lithological constraints on the surrounding rock for the construction of underground water-sealed oil storage caverns, and considering limestone as a potential host rock for such caverns, the dynamic evolution law of fracture aperture in the surrounding rock under hydrodynamic dissolution remains unclear. This study takes the limestone from Yangmu Town, Guangyuan as the research object, replicates the in-situ environment of the storage layer, and systematically investigates the effects of water flow rate and concentration on the dissolution characteristics of limestone fractures through simulated hydrodynamic dissolution tests under in-situ conditions. A dynamic dissolution model was developed based on mass conservation and laminar seepage theory. The results indicate a significant coupling relationship between flow rate and dissolution rate. When the flow rate increases, the difference in concentration between the inlet and outlet decays exponentially, and the mass dissolved per unit time increases sharply. The initial concentration in the solution inhibits dissolution, and when the concentration reaches 34.2 ppm, dissolution is effectively suppressed. The error between the fracture aperture calculated by the theoretical model and the results from 3D scanning is less than 16%, demonstrating that the model can quantitatively characterize the coupling effect. The findings of this study can provide support for predicting water inflow into caverns and conducting safety assessments.